EFL Teachers’ Corrective Feedback and Students’ Revision in a Peruvian University: A descriptive study - Lira Gonzales, Maria Lourdes (2018)
This study explored the EFL teachers’ written corrective feedback (CF) techniques and their EFL students’ ability to integrate the CF while revising their texts. A total of 72 EFL students and 4 EFL teachers participated in this study. The data were collected through explicitation interviews administered to teachers and students, as well as through students’ written productions. A content analysis was carried out employing three pre-established categories: types of students’ errors (Guénette & Lyster, 2013), types of teachers’ feedback (Guénette, 2010), and types of students’ revisions (Ferris, 2006). Results showed that error identification with error code was the most frequent type of written CF used by the two teachers in the pre intermediate groups and one of the teachers in the upper intermediate group; whereas, the other teacher in the upper intermediate group used mainly direct error correction without comment when providing feedback. In addition, results showed that although students from different levels undertook revisions of their errors in different ways, most were ultimately able to correct their errors